Aspect-Based Sentiment Analysis on Twitter Using Bidirectional Long Short-Term Memory - Rizki Annas Sholehat; Erwin Budi Setiawan; Yuliant Sibaroni (Universitas Budi Darma, 2023)
Twitter as one of the social media with the most users in the world, is often used as a medium for sharing opinions that can be positive or negative. Movie reviews containing many complex explanations and judgments will be challenging to classify. Therefore a sentiment analysis process based on aspects is needed to analyze the polarity of film review opinions based on predetermined aspects. This research aims to analyze the polarity of film review opinions based on aspects using the Bidirectional Long Short-Term Memory method and GloVe feature extraction. This study uses plot, acting, and director aspects with a total dataset of 17.247 data. Bidirectional Long Short-Term Memory is proven to produce relevant and accurate results for sentiment analysis with the greatest accuracy of 56,29% in the plot aspect, 87,07% in the acting aspect, and 85,55% in the director aspect. GloVe feature extraction is proven to increase the performance value of this research by up to 13,57% in the plot aspect, 4,16% in the acting aspect, and 10,48% in the director aspect.